Prolonged starvation drives reversible sequestration of lipid biosynthetic enzymes and organelle reorganization in Saccharomyces cerevisiae - Suresh, Harsha Garadi; Silveira dos Santos, Aline Xavier; Kukulski, Wanda; Tyedmers, Jens; Riezman, Howard; Bukau, Bernd; Mogk, Axel (Molecular biology of the cell, 2015)
Cells adapt to changing nutrient availability by modulating a variety of processes, including the spatial sequestration of enzymes, the physiological significance of which remains controversial. These enzyme deposits are claimed to represent aggregates of misfolded proteins, protein storage, or complexes with superior enzymatic activity. We monitored spatial distribution of lipid biosynthetic enzymes upon glucose depletion in Saccharomyces cerevisiae. Several different cytosolic-, endoplasmic reticulum-, and mitochondria-localized lipid biosynthetic enzymes sequester into distinct foci. Using the key enzyme fatty acid synthetase (FAS) as a model, we show that FAS foci represent active enzyme assemblies. Upon starvation, phospholipid synthesis remains active, although with some alterations, implying that other foci-forming lipid biosynthetic enzymes might retain activity as well. Thus sequestration may restrict enzymes' access to one another and their substrates, modulating metabolic flux. Enzyme sequestrations coincide with reversible drastic mitochondrial reorganization and concomitant loss of endoplasmic reticulum-mitochondria encounter structures and vacuole and mitochondria patch organelle contact sites that are reflected in qualitative and quantitative changes in phospholipid profiles. This highlights a novel mechanism that regulates lipid homeostasis without profoundly affecting the activity status of involved enzymes such that, upon entry into favorable growth conditions, cells can quickly alter lipid flux by relocalizing their enzymes.
Gesehen am 25.06.2020